If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(3-z)=12z
We move all terms to the left:
9(3-z)-(12z)=0
We add all the numbers together, and all the variables
9(-1z+3)-12z=0
We add all the numbers together, and all the variables
-12z+9(-1z+3)=0
We multiply parentheses
-12z-9z+27=0
We add all the numbers together, and all the variables
-21z+27=0
We move all terms containing z to the left, all other terms to the right
-21z=-27
z=-27/-21
z=1+2/7
| (-2)^2+4y^2=8 | | 5x-4=12x+16 | | 3x/5+4=5/6x | | 5x-4=22x+16 | | 10m+2.4=6.89 | | (y/2)^2=9 | | 6.4+2.1z(z-2)=8.5 | | -6d-5=31 | | (y/4)^2=36 | | (4y+9)(2-y)=0 | | 8(10-3x)=72-7(3x+1) | | 15n^2-8n=12 | | 9/x=6/7 | | (X+1)^2+16(x+1)+63=0 | | 2x−6=3x+1−x−7 | | 3v-2=2+1/4 | | 75+255c=1605 | | 0.5(x-4)-4x=9(4-x) | | 2h^2+5=12 | | (x-8)^2=9 | | 32x+48=-11x+-77 | | 2(2-2z)-3(2z+6)=z-15 | | -2c-8=-2(-c-8) | | -4x-2(-9+2x)+15=129 | | 1/2(2x−1)=−1/9−7/9 | | 9a-7=-70 | | 3a+2=2a-8 | | B=30-0.05m | | 2x+12=1x+18 | | 2h^2+5h=12 | | g2+23g–24=0 | | 15q2–29q=0 |